Problems and solutions in structural geology and tectonics - Billi, Andrea (Geologist); Fagereng, Å. (Åke) (Developments in structural geology and tectonics ;, 2019)
"Presents students, researchers, and practitioners with an all-new set of problems and solutions commonly faced by structural geologists and tectonics researchers. Topics covered include: the interpretation of structures to understand tectonics, from cross-section balancing to integrating geodesy and geology; inferring strains and stresses from observations; field methods and modern satellite analysis; structural techniques in petroleum geoscience; and novel integration of structural geology and computer science. This book is an essential how-to guide for students of structural geology and tectonics, and can be used as practice and inspiration for professional geologists"--Page 4 of cover